Determining the influencing factors in the residential rooftop solar photovoltaic systems adoption: Evidence from a survey in Qatar - Omar F. Alrawi (19418938) (2022)
Renewable energy sources have developed rapidly, decreased in cost, and proven to have the potential to limit global warming. Renewable energy in the form of solar energy can be collected through decentralized rooftop solar systems. Solar energy development in Qatar is still at an early stage. The abundance of solar radiation, high GDP, and plentiful access to rooftop spaces make rooftop photovoltaic (PV) systems suitable. Unfortunately, the early development and adoption of residential rooftop solar PV systems are expected to face numerous constraints. This paper investigates the factors that impact the residential rooftop solar photovoltaic adoption in Qatar. Through analyzing the response of a general public sample, we hope to prove the hypothesized factors by aiming at testing their solar systems knowledge and awareness. The result of the study will provide insights on how the public perceives solar panels, along with factors the government needs to address to ensure successful public adoption of residential solar rooftop systems in Qatar. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2022.01.064